ROLE OF SMALL INTESTINAL BACTERIAL OVERGROWTH IN THE DYSLIPIDEMIA AND NONALCOHOLIC FATTY LIVER DISEASE PATHOGENESIS - Kvit, K.B. (World of Medicine and Biology, 2024)
Nonalcoholic fatty liver disease is one of the most prevalent chronic liver conditions, often associated with dyslipidemia and metabolic syndrome. Small intestinal bacterial overgrowth is considered a key mechanism potentially contributing to the development of non-alcoholic fatty liver disease and dyslipidemia by affecting metabolic balance, lipid metabolism, and systemic inflammation. This study examined 342 patients with dyslipidemia, assessing the prevalence of small intestinal bacterial overgrowth and its impact on lipid metabolism parameters and inflammatory markers. A significantly higher frequency of small intestinal bacterial overgrowth was found in patients with lipid metabolism disorders (53.4 %) compared to the control group (36 %, p≤0.05) and among those with non-alcoholic fatty liver disease (52 %). Correlation analysis confirmed the association of small intestinal bacterial overgrowth with elevated triglyceride levels, alkaline phosphatase, and insulin resistance index. The findings underscore the significance of small intestinal bacterial overgrowth in the pathogenesis of non-alcoholic fatty liver disease and dyslipidemia, highlighting new opportunities for the diagnosis and treatment of these conditions.
Keywords: nonalcoholic fatty liver disease; small intestinal bacterial overgrowth; dyslipidemia; steatosis; steatohepatitis